Integrative Role of RNA N7-methylguanosine in epilepsy: Regulation of neuronal oxidative phosphorylation, programmed death and immune microenvironment - Jiangli Zhao; Qingyuan Sun; Xuchen Liu; Jiwei Wang; Ning Yang; Chao Li; Xinyu Wang (PLoS ONE, 2025)
Epilepsy is a common brain disease that causes different types of seizures, with an incidence rate of nearly 1%. N7-methylguanosine (m7G) is a prevalent RNA modification that has attracted significant attention in recent research. In this study, we investigated the regulatory pattern and clinical significance of m7G methylation in epilepsy. Gene expression analysis of datasets GSE143272 and GSE190452 identified 8 differentially expressed m7G regulators (NUDT3, EIF4E3, LARP1, IFIT5, SNUPN, METTL1, EIF4A1, and LSM1) in epilepsy. Through consensus clustering, epilepsy patients were divided into two molecular subtypes based on m7G patterns. Enrichment and immune infiltration analyses revealed differences in immune cell infiltration and functions between the two subtypes, particularly in the levels of CD8+ T cells and cytolytic activity. Our findings also suggested that active m7G levels could promote oxidative phosphorylation in the neurons of epilepsy patients and decrease neuronal necroptosis activity. Machine learning algorithms were used to identify key m7G regulators (EIF4E3, NUDT3, SNUPN, LSM1, and METTL1), and a nomogram model was constructed based on these findings. Validation with serums and tissue samples from healthy controls and epilepsy patients confirmed the RNA expression levels of the identified m7G regulators. Overall, this study highlights the important role of m7G regulators in the immune microenvironment, cellular death, and oxidative phosphorylation in epilepsy patients. The insights gained from this research could potentially guide future therapy strategies for epilepsy patients and improve their outcomes.